Assessing the impact of a minimum income scheme: The Basque Country case - Sara de la Rica; Lucía Gorjón (SERIEs - Journal of the Spanish Economic Association, 2019)
In this paper, we evaluate the impact of a minimum income scheme (MIS) in the Basque Country, one of Spain's 17 autonomous regions. In particular, we assess whether the policy delays entry into employment for recipients, as well as the extent to which activating policies aimed at enabling recipients of the MIS to enter employment work. To do so, we use administrative data of the universe of individuals registered in the public employment service in the region. On average, the minimum income scheme does not delay entry into employment, although the impact differs from one demographic group to another. Furthermore, active labour market policies designed for this group, in particular training, have a strong positive impact on finding a new job.
Keywords: C14; C21; C52; 330; Minimum income schemes; Active labour market policies; Poverty; Inverse probability weighting; Propensity score matching